Extremely high frequency Schottky diodes based on single GaN nanowires. (11th June 2023) - Shugurov, K Yu; Mozharov, A M; Fedorov, V V; Blokhin, S A; Neplokh, V V; Mukhin, I S
Abstract: Gallium nitride (GaN) is one of the most promising materials for high-frequency devices owing to its prominent material properties. We report on the fabrication and study of a series of Schottky diodes in the ground-signal-ground topology based on individual GaN nanowires. The electrical characterization of I – V curves demonstrated relatively high ideality factor value (about 6–9) in comparison to the planar Au/GaN diodes that can be attributed to the nanowire geometry. The effective barrier height in the studied structures was defined in the range of 0.25–0.4 eV. The small-signal frequency analysis was employed to study the dependency of the scattering parameters in the broad range from 0.1 to 40 GHz. The approximation fitting of the experimental data indicated the record high cutoff frequency of about 165.8 GHz.